THE EFFECT OF EMOTIONAL INTELLIGENCE, SUSTAINABILITY AWARENESS AND STUDENTS' PERCEPTION OF SUSTAINABLE DEVELOPMENT GOALS FOR ACCOUNTING EDUCATION STUDENTS - Luthfiana Izzaturrahmah; Fauzan, Slamet (Universitas Muhammadiyah Surakarta, 2024)
Important factors in shaping education based on SDGs are education quality, curriculum quality, skill level, education awareness level, knowledge level, intelligence level and learning experience. This study was used to determine the effect of Emotional Intelligence, Sustainability Awareness and Student Perceptions on the goals of Sustainable Development Goals. The implementation of SDGs in higher education is still not optimal, so this research wants to know the importance of SDG's implementation in learning. An explanatory quantitative technique is used in this study. One hundred fifty students from the following universities participated in this study: Malang State University, Surabaya State University, Yogyakarta State University, Jakarta State University, and Indonesian Education University. Sampling method was purposive sampling and data collection using a questionnaire. The results of the research that most dominantly affect the Sustainable Development Goals variable are the Sustainability Awareness (X2) variable of 0.401, Student Perceptions (X3) of 0.337 and Emotional Intelligence (X1) of 0.232. So it is hoped that students' understanding of the SDGs will help them more effectively develop the skills needed for sustainable development.